The doctrine of Christ and its relation to the concept of son of god: a brief study on the nature of Isa a.s. as understood by Indonesia churches - Rashid, Ungaran (IIUM Press, 2019)
"Son of God" is a common term in the Bible, both in the Jewish Scriptures and the New Testament. This term is used to refer to different things: the nation of Israel, the King of Israel, Prophet Adam a.s. or humankind in general, the Messiah (al-Masih), and also Jesus. When the term "son of God" is used to refer to humankind or to Israel, for example, there is no doubt that the term is used figuratively. Nevertheless, when the term is used to refer to Jesus, there is much confusion and misunderstanding among Christians including Indonesian Christians. The Christian community, especially the early Church fathers, made some speculations about the person of Jesus. Unfortunately, the misunderstanding of Christians affects the understanding of Muslims about the term "son of God." Christianity in Indonesia which was introduced by Europeans adopts most of its theology from the West. So, the form of Christianity in Indonesia is similar to the Western or European forms of Christianity, both Protesta nt and Catholic. According to the Christian doctrine of Christ, Indonesian Christians generally and the Indonesian Reformed Church specifically believe that Christ or Messiah (al-Masih) is God who became a man because only God can save human beings on the Day of Judgment